Analisis Jurnal Budaya, Dukungan Keluarga dan Konseling Terhadap Pemilihan Tempat Persalinan : Analysis of Cultural Journals, Family Support, and Counseling on the Choice of Place of Delivery - Anis Marisa (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Data from the Indonesian Ministry of Health said in Indonesia there are about 305/100,00 live births in the Maternal Mortality Rate (AKI). The report found that the location of maternal deaths that occurred was as much as 77% in hospitals, 15,6% at home, 4,1% on the way to health facilities, 2,5% in other health facilities, and 0.8% elsewhere, in the ratio of maternal-infant deaths in West Java province of Cianjur Regency in January-August 2020 recorded 20 cases of maternal deaths with a ratio of 74,28. The results of health ethnographic research in 2012 in Indonesia found there are health problems of mothers and children related to health culture that are quite concerning, such as pregnant women who continue to work until approaching delivery, cutting the umbilical cord with bamboo that is diverted as a knife. Methods: The method used in this study is the cross-sectional approach. Results: The results of the analysis were obtained as many as 29 (86,7%) respondents with low cultural levels chose faskes, 22 (73,3%) respondents with good support chose faskes and 24 (80,0%) respondents with good counseling chose faskes. Statistical test results were obtained values p = 0,000 and OR = 15,600 for cultural influences, p = 0,025 and OR = 5,042 for family support, p = 0,001 and OR = 9,600 for counseling. Discussion: Then it can be drawn that conclusions from all the variables studied is H0 failed to be rejected